Effects of International Customary Law in the Legal Order of the European Union - Kornobis-Romanowska, Dagmara (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The customary provisions in EU law formally may take effect and be enforced within the domestic legal orders of the Member States and internal law of the international organizations. However, the substantive question is if and how the customary international law (in force) may be capable of creating individual rights (direct applicability) with a direct effect in national and EU courts. Also an informal relationship may be observed, when the international law and EU law share the same values and may influence each other. In consideration of the foregoing, the objective of this paper is to analyse the status of the rules in question within the legal regime of the EU (formal perspective), and especially their judicial application in the conditions of complexity and imprecision (substantive perspective), but the essential purpose is to analyse the final legal effect given within the EU regime to the international customary law.
Keywords: prawo zwyczajowe; prawo międzynarodowe; prawo UE